ORAL MUCOCELE (MUCOUS EXTRAVASATION CYST) - Shamim, Thorakkal (Journal of Ayub Medical College Abbottabad, 2009)
A 48-year-old Indian woman presented with a painless lower right lip swelling of size 1Ã—1 cm for two years (Figure-1). The swelling was initially small and slowly increased its size. The overlying mucosa was normal. The swelling was superficial, bluish, fluctuant, soft and non-tender with diffuse margins. She could not recall an episode of trauma to the maxillofacial region. A biopsy was performed and showed areas of spilled mucin surrounded by a granulation tissue with infiltration of chronic inflammatory cells and foamy histiocytes. Dilated salivary gland ducts were also seen in the section (Figure-2). No recurrence was observed at 5 months follow-up examinations.